Genetic profiling of Mycobacterium bovis strains from slaughtered cattle in Eritrea. - Michael Kahsay Ghebremariam; Tiny Hlokwe; Victor P M G Rutten; Alberto Allepuz; Simeon Cadmus; Adrian Muwonge; Suelee Robbe-Austerman; Anita L Michel (Public Library of Science (PLoS), 2018)
Mycobacterium bovis (M.bovis) is the main causative agent for bovine tuberculosis (BTB) and can also be the cause of zoonotic tuberculosis in humans. In view of its zoonotic nature, slaughterhouse surveillance, potentially resulting in total or partial condemnation of the carcasses and organs, is conducted routinely. Spoligotyping, VNTR profiling, and whole genome sequencing (WGS) of M. bovis isolated from tissues with tuberculosis-like lesions collected from 14 cattle at Eritrea's largest slaughterhouse in the capital Asmara, were conducted.The 14 M. bovis isolates were classified into three different spoligotype patterns (SB0120, SB0134 and SB0948) and six VNTR profiles. WGS results matched those of the conventional genotyping methods and further discriminated the six VNTR profiles into 14 strains. Furthermore, phylogenetic analysis of the M. bovis isolates suggests two independent introductions of BTB into Eritrea possibly evolving from a common ancestral strain in Europe.This molecular study revealed the most important strains of M. bovis in Eritrea and their (dis)similarities with the strains generally present in East Africa and Europe, as well as potential routes of introduction of M. bovis. Though the sample size is small, the current study provides important information as well as platform for future in-depth molecular studies on isolates from both the dairy and the traditional livestock sectors in Eritrea and the region. This study provides information onthe origin of some of the M. bovis strains in Eritrea, its genetic diversity, evolution and patterns of spread between dairy herds. Such information is essential in the development and implementation of future BTB control strategy for Eritrea.